A comparative study of intravenous fentanyl and ultrasound-guided femoral nerve block for positioning during spinal anaesthesia in femur fracture surgeries - Rajbala; Sonali Beniwal; Mamta Khandelwal; T Mirthun Thomas (Creative Pharma Assent, 2023)
Objective: To assist in the administration of spinal anesthesia for patients undergoing femur fracture procedures, we conducted comparison research to compare the analgesic efficiency of intravenous fentanyl against ultrasound-guided femoral nerve block (FNB). Material and Methods: A group of 112 patients ranging in age from 18 to 70 years old who had ASA Physical Status I and II and were having femur fracture procedures under spinal anaesthesia participated in the randomised, prospective, interventional trial. These individuals were divided into two groups through a random assignment process. Group FENT (n = 56) received Intravenous fentanyl 1 microgram/kilogram (µg/kg) and five minutes before positioning for spinal anaesthetic, group FNB (n = 56) received ultrasound-guided FNB with 20 millilitres (ml), 1.5% lignocaine and adrenaline (1:200,000). Results: Comparison of pain scores during positioning using the Visual Analog Scale (VAS) revealed that Group FENT had a score of 1.95 ± 0.585, whereas Group FNB had a score of 0.61 ± 0.562 (p-value 0.001). The FNB group demonstrated superior patient positioning quality. Patient satisfaction was similar in both groups, and no significant side effects were observed. Conclusion: FNB offers enhanced analgesia, improved patient positioning, higher patient satisfaction, reduced reliance on additional analgesia, and fewer side effects compared to intravenous fentanyl for spinal anesthesia.